Satellite tracking of sea turtles released after prolonged captivity periods - Mestre, Frederico (2022)
Rehabilitation is an important part of sea turtle conservation, and post-release tracking of the animals is both a way of obtaining information on their movements and behaviour and, at least temporarily, monitoring the success of the rehabilitation process. Two green turtles, Chelonia mydas, and one loggerhead turtle, Caretta caretta, were rehabilitated after long periods in captivity, and their movements followed by satellite tracking after their release near the south of Portugal. Location data were obtained for an average of 688 days after release. All three animals showed a directional movement and the last observed locations coincided with known feeding areas for both species, near the coasts of Mauritania and the state of Ceara, Brazil, for the green turtles, and near Cuba for the loggerhead. Bathymetry, surface currents, wind, sea surface temperature, chlorophyll-a concentration and geomagnetic field were analysed as spatial and environmental variables potentially affecting movement. Only bathymetry, sea surface temperature and geomagnetic variables showed significant association with the path choice. This project supports the notion that sea turtles have the ability to survive in the wild after long periods in captivity and to return to the species' known feeding areas, justifying the effort in their rehabilitation and post-release tracking.